x^2*2^x
x^((2*2)^x)
2 x x *2
d / 2 x\ --\x *2 / dx
Применяем правило производной умножения:
ddxf(x)g(x)=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x} f{\left(x \right)} g{\left(x \right)} = f{\left(x \right)} \frac{d}{d x} g{\left(x \right)} + g{\left(x \right)} \frac{d}{d x} f{\left(x \right)}dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=x2f{\left(x \right)} = x^{2}f(x)=x2; найдём ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
В силу правила, применим: x2x^{2}x2 получим 2x2 x2x
g(x)=2xg{\left(x \right)} = 2^{x}g(x)=2x; найдём ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
ddx2x=2xlog(2)\frac{d}{d x} 2^{x} = 2^{x} \log{\left(2 \right)}dxd2x=2xlog(2)
В результате: 2xx2log(2)+2⋅2xx2^{x} x^{2} \log{\left(2 \right)} + 2 \cdot 2^{x} x2xx2log(2)+2⋅2xx
Теперь упростим:
2xx(xlog(2)+2)2^{x} x \left(x \log{\left(2 \right)} + 2\right)2xx(xlog(2)+2)
Ответ:
x x 2 2*x*2 + 2 *x *log(2)
x / 2 2 \ 2 *\2 + x *log (2) + 4*x*log(2)/
x / 2 2 \ 2 *\6 + x *log (2) + 6*x*log(2)/*log(2)